PISA Under the Spotlight: Science Literacy Levels of Junior High Students in Samarinda - Nurul Fitriyah Sulaeman; Zulkarnanen; Atin Nuryadin; Nurul Wahdah (Program Studi Pendidikan Fisika, 2026)
Science literacy is a fundamental competency measured by the Programme for International Student Assessment (PISA) and serves as a global indicator of science education quality. This study aims to analyze the science literacy levels of junior high school students in Samarinda based on the PISA framework, and to examine differences based on gender, school location, and school accreditation. The study employed a descriptive-quantitative approach involving students from two schools: SMPN 4 Samarinda (Accreditation A, urban) and SMPN 19 Samarinda (Accreditation B, suburban). Research instruments included PISA-based items from level 1b to level 6, and interview guidelines for science teachers. The results revealed student completion percentages across PISA levels: level 1b (98%), level 1a (78%), level 2 (62%), level 3 (48%), level 4 (29%), level 5 (18%), and level 6 (21%). Significant differences were found based on gender, with male students outperforming female students. Urban school students achieved higher average scores than suburban students, and schools with Accreditation A demonstrated higher science literacy levels compared to Accreditation B schools. Interview results with science teachers indicated the need to strengthen teacher capacity in implementing PISA-aligned science curricula and developing appropriate evaluation instruments. This study is expected to serve as a reference for policymakers in designing strategies to improve science education quality in the region.